Prevalence and role of Type six secretion system in pathogenesis of emerging zoonotic pathogen Helicobacter pullorum from retail poultry. Issue 6 (2nd November 2019) - Javed, Kashaf; Gul, Farzana; Abbasi, Rashda; Zaidi, Rabbia Abbas; Noreen, Zobia; Bokhari, Habib; Javed, Sundus
ABSTRACT: Helicobacter pullorum is an emerging zoonotic pathogen that causes gastroenteritis in chickens and inflammatory bowel disease in humans ingesting contaminated meat. However, the mechanism by which the bacterium causes disease is unclear. Type six secretion system (T6SS) plays a major role in bacterial pathogenesis and adaptation. Haemolysin coregulated protein (Hcp) plays a central role in the structure of the T6SS pilus and acts as effector protein in certain bacteria. In this study, H. pullorum isolated from 156 caecal samples of broiler chickens was screened for the presence of T6SS Hcp gene via PCR amplification. 30.7% of caecal and 18.3% of liver samples tested positive for presence of H. pullorum . From these positive samples, 29.7% possessed the T6SS gene. In bacterial co-culture experiments, significant loss of viability (81.6–39.1%) was observed for H. pullorum -infected hepatocytes and presence of Hcp did not contribute to the loss of cell viability. Nevertheless, infection of erythrocytes with Hcp-positive isolates was associated with greater haemolytic activity compared to infection with Hcp-negative isolates. Therefore, presence of T6SS could be indicative of virulent strains meriting further studies to characterize this virulence factor in H. pullorum infection.